A New Approach to Regulating Temporary Agency Work in Ontario or Back to the Future? - Vosko, Leah F. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
In 2009, the province of Ontario, Canada adopted the Employment Standards Amendment Act (Temporary Help Agencies) partly in response to public concern over temporary agency workers’ limited access to labour protection. This article examines its “new” approach in historical and international context, illustrating that the resulting section of the Employment Standards Act (ESA) reflects continuity through change in its continued omissions and exclusions.The article begins by defining temporary agency work and describing its significance, explaining how it exemplifies precarious employment, partly by virtue of the triangular employment relationship at its heart. Next it traces three eras of regulation, from the early 20th to the early 21st centuries: in the first era, against the backdrop of the federal government’s forays into regulation through the Immigration Act, Ontario responded to abusive practices of private employment agencies, with strict regulations, directed especially at those placing recent immigrants in employment. In the second era, restrictions on private employment agencies were gradually loosened, resulting in modest regulation; in this era, there was growing space for the emergence of “new” types of agencies providing “employment services,” including temporary help agencies, which carved out a niche for themselves by targeting marginalized social groups, such as women. The third era was characterized by the legitimization of private employment agencies and, in particular, temporary help agencies, both in a passive sense by government inaction in response to growing complexities surrounding their operation, and in an active sense by the repeal of Ontario’s Employment Agencies Act in 2000.Despite a consultative process aimed, in the words of Ontario’s then Minister of Labour, at “enhanc [ing] protections for employees working for temporary help agencies,” the new section of the ESA adopted in 2009 reproduces outdated approaches to regulation through its omissions and exclusions; specifically, it focuses narrowly on temporary help agencies rather than including an overlapping group of private employment agencies with which they comprise the employment services industry and its denial of access to protection to workers from a particular occupational group (i.e., workers placed by a subset of homecare agencies otherwise falling within the definition of “assignment employees”). Highlighting the importance of looking back in devising new regulations, the article concludes by advancing a more promising approach for the future that would address more squarely the triangular employment relationship as the basis for extending greater protection to workers.